Optimization of Process Parameters for L-Glutaminase Production by Pseudomonas Species ALG3 - , J. Okpalla; , L. O. Dim; , D. A. Onyekuru; , I. E. Duru; , T. O. Mba (Archives of Current Research International, 2022)
The present study reports the optimization of process parameters for L-glutaminase production by Pseudomonas species ALG3. The L-glutaminase –producing bacterium had already been isolated from soil at a location within Chukwumemeka Odumegwu Ojukwu University, Uli in Anambra state. It was identified using cultural, biochemical and molecular characteristics. Optimization of L-glutaminase production was done by assessing the effect of various parameters using mineral salt medium contained in 250 ml flasks. The parameters included various bivalent metals, pH, surfactants, growth promoters, amino acids and fermentation time. The Results showed that the addition of FeSO4 stimulated optimum L-glutaminase yield of 38.36 U/ml by Pseudomonas species ALG3, while the least production was observed with MnSO4. Enhanced L-glutaminase yield of 30.73 U/ml was recorded at pH 8.0, while the lowest enzyme accumulation was observed at pH 9.0. The highest L-glutaminase accumulation of 82.25 U/ml was achieved with Tween 80, while the lowest yield was recorded with stearic acid. Urea, stimulated maximum L- Glutaminase yield of 43.82 U/ml, while minimum accumulation was observed with peptone. Proline stimulated highest L- glutaminase yield of 42.63U/ml, while the lowest yield was observed with tyrosine. Highest L- glutaminase yield (91.88 U/ml) was observed after 72h, the yield decreased thereafter. The results obtained in the study illustrated that the optimization of process parameters, increased appreciably the L-glutaminase yield of Pseudomonas species ALG3. This suggest that Pseudomonas species can be used for large scale production of L- glutaminase, which can offer great potential for applications in Medicine and food industry.